The Pengaruh Jarak Tanam Tergadap Pertumbuhan Mangrove Hasil Rehabilitasi di Lampung Timur - Amanta, Neysa Nurma; Kusmana, Cecep; Kintamani, Endang; Hafidhin, Dimas (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2025)
Mangrove ecosystems are essential for maintaining coastal ecological stability, yet they remain highly vulnerable to degradation due to increasing anthropogenic pressures. Rehabilitation efforts are a strategic step in restoring the ecological functions of these areas. This study was conducted to evaluate mangrove planting through growth parameters and to analyze the effect of planting distance on the growth of 11-month-old Rhizophora apiculata at a rehabilitation site in Purworejo Village, East Lampung. The survival rate at a planting distance of 1×1 m (95%) and 2×2 m (85%) showed good results, while at a planting distance of 1×2 m (68.3%) showed less favorable results. The stem height measurements indicated that the highest average was at a planting distance of 1×1 m (41.9 cm), followed by 2×2 m (36.7 cm), and 1×2 m (27.2 cm). In contrast, the diameter measurements showed that the largest average was at a planting distance of 1×1 m (1.17 cm), 2×2 m (1.10 cm), and 1×2 m (0.84 cm). Analysis of variance shows that the appropriate planting distance arrangement can improve the efficiency of space utilization and nutrient availability, as well as contribute to the structural growth of mangroves in the early phase.